Sema3A ameliorates the pathological progression of osteoarthritis by modulating mitochondrial damage in chondrocytes: Effect of Sema3A on chondrocytes in osteoarthritis - Guo, Zhongkui; Qin, Yong; Li, Yi; Tang, Peifu (Cellular and Molecular Biology, 2024)
Osteoarthritis (OA) is a major disease that causes disability in middle-aged and elderly people. A comprehensive understanding of its pathogenesis is of great significance in finding new clinical diagnosis and treatment schemes. The role of Semaphorin 3A (Sema3A) in OS has attracted attention recently, and the purpose of this study is to analyze the mechanisms underlying its impact on OS. First, a rat model of OS was established. Hematoxylin-eosin (HE) and TUNEL staining showed that the modeled rats presented typical pathological manifestations of OS, confirming the success of the modeling. Sema3A was significantly underexpressed in OS rats. Subsequently, Sema3A abnormal expression vectors were constructed to intervene in chondrocytes isolated from OS rats. It was found that the proliferation of chondrocytes was decreased, the apoptosis was increased, and the mitochondrial damage and autophagy were intensified after silencing Sema3A expression, while the above pathological processes were reversed when Sema3A expression was increased. In conclusion, Sema3A has an important influence on the pathological progression of OS, and molecular therapies targeting to increase Sema3A expression may become a new treatment for OS in the future.